Working Memory Capacity and Psychotic-Like Experiences in a General Population Sample of Adolescents and Young Adults - Ziermans, Tim (Frontiers in Psychiatry, 2013)
Working memory (WM) impairment is a common feature in individuals with schizophrenia and high-risk for psychosis and a promising target for early intervention strategies. However, it is unclear to what extent WM impairment parallels specific behavioral symptoms along the psychosis continuum. To address this issue, the current study investigated the relation of WM capacity with psychotic-like experiences (PLEs) in a large Swedish population sample (N = 1012) of adolescents and young adults (M = 24.4 years, range 12-35). WM was assessed with two online computer tasks: A task where participants had to identify and remember the location of an odd shape and a task of remembering and following instructions. PLE scores were derived from a translated symptom questionnaire (Community Assessment of Psychic Experiences; CAPE), which includes positive, negative and depressive symptom scales. Positive and negative symptom scales were further subdivided into symptom clusters based on factor analyses. The results showed that low WM capacity was modestly associated with increased reports of bizarre experiences and depressive symptoms, after controlling for age, gender, and global symptom scores. Interestingly, when analyses were repeated for separate age groups, low WM was exclusively associated with a higher frequency of bizarre experiences for young adults (20 - 27 years) and with depressive symptoms for older adults (28 - 35 years). These findings suggest that specific PLEs can be indicative of reduced WM capacity in early adulthood, which in turn may reflect an increased risk for psychosis and a greater need for targeted intervention. In contrast, during adolescence individual differences in cognitive development may influence the strength of the relationships and thereby mask potential vulnerabilities for psychopathology.